High-fat diet triggers obesity-related early infiltration of macrophages into adipose tissue and transient reduction of blood monocyte count. (January 2020) - Liu, Yanxia; Lu, Xinping; Li, Xialian; Du, Peijie; Qin, Guijun
Highlights: HFD induced obesity, dramatic fat expansion, and accumulation of ATMs in mice. HFD-induced changes in VAT were partially reversed upon reverting to ND for 6 weeks. Transient reduction of blood monocyte count was seen at early stages of HFD feeding. Blood monocytes could be targeted as a new obesity treatment. Abstract: Infiltration of adipose tissue macrophages (ATMs) is a typical feature of obesity, and circulating immune cells may indicate immune cell accumulation. However, it remains unclear whether this is true in the early stages of obesity. This study aimed to define the role of blood monocytes in obesity and the relationship between blood monocytes and ATMs in early-stage obesity. Two groups of male C57BL/6 J mice were fed on a 60 % high-fat diet (HFD) or a 10 % fat normal diet (ND), respectively, and monitored at 1, 2, 3, 7, and 12 weeks. Populations of circulating blood monocytes (CD11b + CD115+), ATMs (F4/80+CD11b+), and their subtypes were collected and analyzed using flow cytometry and immunofluorescence. Some cytokines (TNF-a, IL-1β) and chemokines (CCL2, CCL7) were also analyzed by real-time PCR. HFD induced obesity, dramatic fat expansion, and accumulation of ATMs in mice after 12 weeks. However, an acute and transient reduction of circulating monocyte count, elevated expression of CD11c in ly6c low monocytes, and concurrent infiltration of ATMs into visceral adipose tissues (VAT) were observed as early as 1 week after initiating HFD. Further, HFD-induced changes in VAT, but not blood monocyte count, were partially reversed upon reverting to ND for 6 weeks. An acute but transient reduction of blood monocyte count was observed at the early stages of HFD feeding, which might be related to early infiltration of macrophages into adipose tissues. We believe that blood monocytes could be targeted as a new obesity treatment following additional studies.